The Effect of Motivation and Organizational Climate on Performance of Employees at The Bureau Of Public Relations and Protocol of Regional Secretariat of Maluku Province - Muhamad Arsad Rahawarin; Hendry Selanno; Rugaya Al hamid (Program Pascasarjana Universitas Negeri Makassar, 2022)
ABSTRACTThis study aims to analyze the magnitude of the influence of work motivation and organizational climate on the performance of employees of the Bureau of Public Relations and Protocol of Regional Secretariat of Maluku Province. The approach used in this research is quantitative approach. The population in this study is all employees in the Bureau of Public Relations and Protocol Secretariat of Maluku participating 40 people. The sample is part of the population or part of the number and characteristics of the population. A sample of 25 people were determined randomly based on the sample tables of Issac and Michael. Data were analyzed by multiple linear regression. The result of the research shows that (1) work motivation consisting of salary, job itself, promotion, supervision and organization climate consisting of responsibility, identity, warmth, support, conflict simultaneously has positive and significant effect to employee performance, (2) salary is a variable of work motivation factors that has a positive and significant influence and the most dominant on employee performance and (3) Warmth is a variable of organizational climate factors that has a positive and significant influence and second dominant to the performance of the Bureau of Public Relations and Protocol of Regional Secretariat of Maluku Province.